2008
DOI: 10.1183/09031936.00087608
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for chronic thromboembolic pulmonary hypertension

Abstract: Chronic thromboembolic pulmonary hypertension (CTEPH) is characterised by nonresolving pulmonary thromboemboli that can be treated by surgical pulmonary endarterectomy (PEA). The authors of the present study sought to confirm known and to identify novel CTEPH risk factors in a controlled retrospective cohort study of prevalent CTEPH cases collected in three European centres offering PEA.Data from CTEPH patients were compared with nonthromboembolic pre-capillary pulmonary arterial hypertension cohorts at the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
279
5
30

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 362 publications
(337 citation statements)
references
References 113 publications
14
279
5
30
Order By: Relevance
“…Data from three European specialist centres have shed light on risk factors for CTEPH by comparing patients with CTEPH and those with pulmonary arterial hypertension [16]. In addition to previously established risk factors, such as a history of pulmonary embolism, deepvein thrombosis, ventriculo-atrial shunt, infected pacemakers and splenectomy [16,17], the study identified novel factors associated with CTEPH, such as thyroid replacement therapy and a history of malignancy. Other established risk factors include myeloproliferative disorders and inflammatory bowel disease [2].…”
Section: Diagnosis Of Ctephmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from three European specialist centres have shed light on risk factors for CTEPH by comparing patients with CTEPH and those with pulmonary arterial hypertension [16]. In addition to previously established risk factors, such as a history of pulmonary embolism, deepvein thrombosis, ventriculo-atrial shunt, infected pacemakers and splenectomy [16,17], the study identified novel factors associated with CTEPH, such as thyroid replacement therapy and a history of malignancy. Other established risk factors include myeloproliferative disorders and inflammatory bowel disease [2].…”
Section: Diagnosis Of Ctephmentioning
confidence: 99%
“…Routine haematological and biochemical tests are usually unremarkable in patients with CTEPH, although lupus anticoagulant/anti-cardiolipin antibodies have been identified in 10-20% of CTEPH patients [16,20]. There is also some indication of an increased thrombophilic tendency [21,22].…”
Section: Diagnosis Of Ctephmentioning
confidence: 99%
“…Geçirilmiş splenektomi öyküsü, hidrosefali tedavisi için uygulanan ventriküloatriyal şant, miyeloproliferatif hastalıklar ve kronik inflamatuvar barsak hastalığı, osteomiyelit gibi diğer kronik inflamatuvar durumların varlığında artmış KTEPH riski olduğu bildirilmektedir. Bu durumlarla KTEPH arasındaki ilişkinin mekanizması tam olarak aydınlatılamamakla birlikte kronik inflamasyon ya da infeksiyonun rol oynayabileceği düşünülmektedir (8). Kötü prognoz için ortalama pulmoner arter basıncı eşik değeri 30 mm Hg, tanı sıra-sında ortalama pulmoner arter basıncı 40 mm Hg'dan fazla olan hastalar için 5 yıllık yaşam ise %30 olarak bildirilmektedir (9,10).…”
Section: Introductionunclassified
“…An increased risk of CTEPH was associated with prior splenectomy (odds ratio (OR) 13, 95% confidence interval (CI) 2.7-127), ventriculo-atrial shunt for the treatment of hydrocephalus (OR 13, 95% CI 2.5-129) and chronic inflammatory disorders, such as osteomyelitis and Crohn's disease (OR 67, 95% CI 7.9-8,832). A further study also identified splenectomy as a risk factor for CTEPH [27], and a recent retrospective cohort study involving 687 patients with CTEPH showed that thyroid replacement therapy (OR 6.10, 95% CI 2.73-15.05) and a history of malignancy (OR 3.76, 95% CI 1.47-10.43) were novel risk factors for CTEPH [28].…”
Section: Pathogenesis Risk Factors and Vascular Biologymentioning
confidence: 99%